2001
DOI: 10.1002/app.10013
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and physical properties of closed cell microcellular ethylene–octene copolymer: Effect of precipitated silica filler and blowing agent

Abstract: ABSTRACT:The morphology of the microcellular ethylene-octene copolymer (Engage) of both unfilled and precipitated silica-filled compounds was studied from SEM photomicrographs with variation of blowing agent and silica filler loading. The average cell size, maximum cell size, and cell density varies with variation of blowing agent and filler loading. Physical properties similar to relative density, hardness, tensile strength, elongation at break, modulus, and tear strength decreases with blowing agent concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…So, the intensity of the tear propagation is much higher at these points when compared with the bulk of the specimen. It can also be observed that the absence of tear lines as observed by Nayak and Tripathy [10] in silica-filled poly(ethylene octane) microcellular vulcanizates who attributed it to the occurrence of delamination between the filler and the polymer matrix. However in our case, irrespective of blowing agent and cross linking loadings, it can be observed that in all the fracture microphotographs there are no tear lines.…”
Section: Effect Of Pressurementioning
confidence: 80%
See 1 more Smart Citation
“…So, the intensity of the tear propagation is much higher at these points when compared with the bulk of the specimen. It can also be observed that the absence of tear lines as observed by Nayak and Tripathy [10] in silica-filled poly(ethylene octane) microcellular vulcanizates who attributed it to the occurrence of delamination between the filler and the polymer matrix. However in our case, irrespective of blowing agent and cross linking loadings, it can be observed that in all the fracture microphotographs there are no tear lines.…”
Section: Effect Of Pressurementioning
confidence: 80%
“…This observation is contrary to the generally known principle that increasing blowing-agent loadings leads to rapid increase in nucleation rates, thereby leading to the formation of increasing number of cells. Nayak and Tripathy [1,9,10] widely reported that the phenomenon of increase in the number of cells can be related to the nucleation by dispersed filler phase, and variation in cell size can be attributed to the melt viscosity. The filler used in the present system is a polymeric filler 9WGRT powder, which does not retard the growth of cells as a rigid fillers (silica and carbon blacks), leading to no appreciable change in the number of cells.…”
Section: Effect Of Blowing Agentmentioning
confidence: 99%
“…The torque difference shows shear dynamic modulus that indirectly relates to the crosslink density of the compounds. However, because of the decomposition of blowing agent which releases gas, the cure characteristics of rubber including blowing agent obtained on MDR are interfered with by gas dissolving under high pressure and/or forming microbubbles in the rubber phase 15, 18–20. To eliminate the false appearance, rubber compounds measured for vulcanization parameters excluded the blowing agents.…”
Section: Methodsmentioning
confidence: 99%
“…Polyethylene–octene elastomer (POE), a metallocene‐based polyolefin used as a novel polyolefin elastomer, is widely used in applications such as sheets, automotive parts, durable goods, modifiers in engineering plastics, and wires and cables because of its good balance of mechanical properties and favorable processability 19–21. However, POE foams have been seldom researched up to now 22–25…”
Section: Introductionmentioning
confidence: 99%